Austria : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
Growth in the Austrian economy decelerated in mid-2000 in tandem with weaker activity in Europe after a vigorous expansion. Privatization of state holdings in commercial enterprises has continued, and liberalization of the electricity and gas markets is planned to be completed well ahead of EU deadlines. In light of pressures to reduce the tax burden and narrow the scope of the public sector's direct economic involvement, Executive Directors recommended a long-term focus on the fiscal policy debate and encouraged the authorities for their civil service.